PENGARUH KEMAMPUAN MANAJERIAL, KUALITAS PELAYANAN, DAN KEMAMPUAN MENGAJAR TERHADAP MUTU PENDIDIKAN DI MADRASAH ALIYAH AL FALAH KECAMATAN PASEAN KABUPATEN PAMEKASAN - jurnalmap map; Moh. Khairul Anwar Luris; Cathrine Sri Hartati; Hidayat ÔÇì (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2020)
ABSTRACT The purpose of this study is 1) To describe about managerial ability, service quality, teaching ability and education quality, 2) To find out whether managerial capability, service quality and teaching ability have simultaneous influence to the education quality, 3) To find out whether managerial skills, service quality and teaching ability have partial influence on improving the quality of education, 4) To know which variable between managerial ability, service quality and teaching ability have dominant influence to of education quality. The results showed that simultaneously, managerial ability, service quality, and teaching ability simultaneously have a significant influence on the quality of education. Partially, managerial ability, service quality and partial teaching ability have a significant influence on the quality of education. Service quality has dominant effect to the of education quality in Madrasah Aliyah Al Falah Kec. Pasen Kab. Pamekasan. Keywords: Managerial Capability, Service Quality, Teaching Capability and Education Quality